New Horizons for Industry 4.0 in Modern Business - Nayyar, Anand; Naved, Mohd.; Rameshwar, Rudra (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book discovers what it will take to reindustrialize the previous industrial powerhouses in order to offset the advantages of cheap labor suppliers dominating the industrial sector by exploring the current situation of the production, processing, and manufacturing industries. The Internet of Things (IoT), Big Data, Cyber-Physical Systems (CPS), and Cloud Computing, Cyber Security, Cobotics, Automation, AI, 3D Printing and Additive Manufacturing, SDN, Blockchain technologies are outlined in this unique and comprehensive book, which has true potential for professionals, researchers, policymakers, and book users. New Horizons for Industry 4.0 in Modern Business encompass trends in business and technology globally that may completely alter how manufacturing and production are conducted. What you will discover: Learn about the Industrial Internet of Things and the Industrial Internet. Learn about the technologies that must develop to support Industry 4.0 and what is being done right now to make that happen. In this book, the topic of Industry 4.0 is covered in detail, and it even moves on to concepts of Digital Twins to boost output and create Industrial Internet of Things. With the development of new digital industrial technology, or "Industry 4.0," it is now feasible to collect and analyze data from many machines, resulting in processes that are quicker, more adaptable, and more efficient, producing things of higher quality while spending less money. The manufacturing revolution will boost productivity, alter economics, promote industrial development, and alter workforce demographics, ultimately altering the competitiveness of businesses and areas. Although advanced digital technology is being employed in manufacturing, Industry 4.0 will completely change how things are done. Greater production efficiencies will result, and conventional connections between suppliers, manufacturers, and consumers-as well as between people and machines-will shift. Industry 4.0 is changing the business process. This disruptive technology is radically changing the way businesses/manufacturing is conducted. It will give machines that little bit of intuition with the help of robotics, 3D printing, artificial intelligence, augmented reality, and virtual reality-that will help them do mindless and repetitive jobs without human intervention, allowing humans to focus more on their core competencies.
Foundation Concepts for Industry 4.0 -- PROSPECTIVE APPLICATION OF BLOCKCHAIN IN MUTUAL FUND INDUSTRY -- Waste Management 4.0- An Industry 4.0 Approach to the Future Waste Management System -- Artificial Intelligence Powered Automation for Industry 4.0 -- To Trust or not to Trust Cybots: Ethical Dilemmas in the Posthuman Organization -- Business Sustainability and Growth in Journey of Industry 4.0- A Case Study -- Challenges and opportunities for mutual fund investment and the role of industry 4.0 to recommend the individual for speculation -- Blockchain Based Secure Manufacturing Network Management for Industry 4.0 -- AIC Algorithm for Using Intention of Online Food Delivery Services in Industry 4.0: Evidence from Vietnam -- Design and Automation of Hybrid Quadruped Mobile Robot for Industry 4.0 Implementation -- Hydrogel based on alginate as an ink in Additive Manufacturing technology - processing methods and printability enhancement -- Industry 4.0 Internet of Medical Things Enabled Cost Effective Secure Smart Patient Care Medicine Pouch -- 3D PRINTING PATHWAYS FOR SUSTAINABLE MANUFACTURING -- IMPLEMENTING DIGITAL AGE EXPERIENCE MARKETING TO MAKE CUSTOMER RELATIONS MORE SUSTAINABLE -- 3D Printing: A Game Changer for Indian MSME Sector in Industry 4.0 -- ROLE OF 3D PRINTING IN THE PHARMACEUTICAL INDUSTRY.
Keywords: Sustainability; Cooperating objects (Computer systems).; Cloud Computing; Internet of things; Blockchains (Databases).; Sustainability; Cyber-Physical Systems; Cloud Computing; Internet of Things; Blockchain